Exercise intensity and technical demands of small-sided games in young Brazilian soccer players: effect of number of players, maturation, and reliability - da Silva, C. D.; Impellizzeri, F. M.; Franco, M.; Natali, A. J.; de Lima, J. R. P.; Bara-Filho, M. G.; Silami-Garcia, E.; Marins, J. C. B. (The Journal of Strength and Conditioning Research, 2011)
The aims of this study were to examine in young soccer players (a) the effect of varying the number of players on exercise intensity (EI) and technical actions during small-sided games (SSGs), (b) the reliability of EI and technical actions, and (c) the influence of the players' maturation on EI and involvements with the ball (IWBs). Sixteen male soccer players (mean ± SD; age 13.5 ± 0.7 years, height 164 ± 7 cm, and weight 51.8 ± 8 kg) completed 2 bouts of 3 vs. 3 (SSG3), 4 vs. 4 (SSG4), and 5 vs. 5 (SSG5) training. Exercise intensity was measured using heart rate and expressed as a percentage of maximal heart rate (%MHR). Technical actions were quantified from video recordings. Maturation stage was determined with the Tanner scale. Exercise intensity in SSG3 (89.8 ± 2%MHR) was higher (p < 0.003) than that in SSG5 (86.9 ± 3%MHR). The EI in the first set (86.8 ± 4%MHR) was lower (p < 0.001) than that in the second (89.1 ± 3%MHR) and in the third set (89.4 ± 3%MRH). No effects of number of players were found in IWB, passes, target passes, tackles, and headers. Significantly more crosses, dribbling, and shots on goal were observed during SSG3 compared to during SSG4 or SSG5 (p < 0.05). The typical error for EI, expressed as coefficient of variation, ranged from 2.2 to 3.4%. The reliability for the most frequent technical actions ranged from 6.8 to 19.3%. The level of maturation was not correlated with either EI or IWB. These results extend previous findings with adult players suggesting that SSGs can provide an adequate training stimulus for young players and are feasible for groups with heterogeneous maturation levels.